Recovery audit contractor audits and appeals at three academic medical centers. Issue 4 (24th February 2015) - Sheehy, Ann M.; Locke, Charles; Engel, Jeannine Z.; Weissburg, Daniel J.; Mackowiak, Stephanie; Caponi, Bartho; Gangireddy, Sreedevi; Deutschendorf, Amy
<x xml:space="preserve">Abstract</x> BACKGROUND Outpatient (observation) and inpatient status determinations for hospitalized Medicare beneficiaries have generated increasing concern for hospitals and patients. Recovery Audit Contractor (RAC) activity alleging improper status, however, has received little attention, and there are conflicting federal and hospital reports of RAC activity and hospital appeals success. OBJECTIVE To detail complex Medicare Part A RAC activity. DESIGN, SETTING AND PATIENTS Retrospective descriptive study of complex Medicare Part A audits at 3 academic hospitals from 2010 to 2013. MEASUREMENTS Complex Part A audits, outcome of audits, and hospital workforce required to manage this process. RESULTS Of 101, 862 inpatient Medicare encounters, RACs audited 8110 (8.0%) encounters, alleged overpayment in 31.3% (2536/8110), and hospitals disputed 91.0% (2309/2536). There was a nearly 3‐fold increase in RAC overpayment determinations in 2 years, although the hospitals contested and won a larger percent of cases each year. One‐third (645/1935, 33.3%) of settled claims were decided in the discussion period, which are favorable decisions for the hospitals not reported in federal appeals data. Almost half (951/1935, 49.1%) of settled contested cases were withdrawn by the hospitals and rebilled under Medicare Part B to avoid the lengthy (mean 555 [SD 255] days) appeals process. These original inpatient claims are considered improper payments recovered by the RAC. The hospitals also lost appeals (0.9%) by missing a filing deadline, yet there was no reciprocal case concession when the appeals process missed a deadline. No overpayment determinations contested the need for care delivered, rather that care should have been delivered under outpatient, not inpatient, status. The institutions employed an average 5.1 full‐time staff in the audits process. CONCLUSIONS These findings suggest a need for RAC reform, including improved transparency in data reporting. Journal of Hospital Medicine 2015;10:212–219. © 2015 Society of Hospital Medicine.